Achievements of Nursing Portal Development in Selected Countries - Zahra Azadmanjir; Niloufar Masoori; Mohammad Ali Cheraghi; Reza Safdari; Mashaallah Torabi (Tehran University of Medical Sciences, 2011)
Background & Aim: Web-based technologies provide new opportunities for education, research and professional development of nursing. Nurses have few opportunities to use the Internet due to managers' obligations not to use the Internet in work hours, and their traditional attitudes to nursing practice. Establishment of a national nursing portal is a useful way to resolve some of these problems. The purpose of the present study was to investigate the experiences of development of nursing portals in some countries and provide helpful recommendations. Methods & Materials: This was a descriptive- comparative study. Using systematic review of the literature, the least features for nursing portal structures and contents were identified. Then, the identified features were assessed in selected countries through observation or communication with the portal board. Results: Personalization, user's profile, search engine, platform-independent display, SSO capability, security mechanisms and collaborative capabilities, clinical guidelines, continuing education, electronic learning courses, and evidence-based nursing processes were common features in the nursing portals. Conclusion: Development of a specialized comprehensive portal that has all of the desirable features can be achieved through clear definitions of strategies on portal development, maintenance, and analysis of user's requirements. The main requirement to integrate services and contents provided by the portal include specific and integrated structure of all entities in nursing services systems.